Consumer profile, consumer demand and market of online businesses in Iloilo City - Asessor, Thea Marie; Bañares, Christine Nicole A.; Benarao, Aira Marie E.; Canto, Conrado III, C.
The study determines the profile of online consumers such as their age, civil status, occupation and yearly income. It also identifies the demand of online consumers in terms of their need, product preference and purchasing habits. It also looks at the online market such as the trends, product type and the suppliers. The respondents of the study included fifty online consumers, comprising equally of both male and female, identified using convenience sampling technique. Descriptive analysis was made on the major variables of the study. Online consumers that often have access online are in the age of group of 20-29. These are composed mostly of students and professionals who are in college or have graduated in college. Most online consumers who responded are single with a yearly income of Php 0-50,000, which indicates that they spend more time surfing on the internet. In terms of demand for online businesses in Iloilo City, a big percentage of consumers are confident in buying goods and services online but do so with a bit of caution. Consumers also avail of the services of online shops using them to mostly purchasing items such as clothing and electronic gadgets. Also purchased are items such as food, jewelry, cosmetics, and plane tickets among others. Rewards and loyalty system of a traditional store are the most important factors consumers consider in their decision to purchase items. In contrast, effective product presentation is seen as the most influential factor in purchasing decisions for online consumers. As to the purchasing habits of online consumers, mostly purchase items only once a year, choosing Lazada as their usual go-to online shop. Most consumers are willing to spend around Php 1000-5000 when purchasing online and cited clarity of product information as the most common feature between online stores. Online consumers identified that online trade are convenient, offers big discounts and promos and quick in their delivery services. However, they also said that online purchases are risky, delays in the delivery are inevitable causing a longer waiting time, and they are unable to see and test the product having no assurance of the quality. Lack of communication between the seller and buyer is also a drawback of online purchase.
Research Paper (BA 199 - Business Research). -- Iloilo City : University of the Philippines Visayas - College of Management, [n.d.]